2011
DOI: 10.1177/1468798411430101
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally appropriate New Media Literacies: Supporting cultural competencies and social skills in early childhood education

Abstract: Young children explore their world through manipulatives, playing with ‘technology’ that may or may not be digital. To this end, I offer an exploration into how the existing framework of the New Media Literacies (NMLs) paradigm set forth by Henry Jenkins (2006) in Confronting the Challenges of Participatory Culture: Media Education for the 21st Century might be applicable to early childhood education. For the purposes of this paper, I focus on three of the twelve NML skills (play, distributed cognition and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 52 publications
1
32
1
9
Order By: Relevance
“…Similarly, Sarah told Laura that she participated in an online forum for parents and regularly received emails regarding a child's healthy development. Thus, although Alper (2011) found that families from middle to higher socioeconomic statuses might not fully support new media use "due to 'moral panics' regarding popular culture and digital technologies" (p. 180), our findings suggest that parental concerns are socially constructed and are not specific to socio-economic status.…”
Section: Discussioncontrasting
confidence: 75%
“…Similarly, Sarah told Laura that she participated in an online forum for parents and regularly received emails regarding a child's healthy development. Thus, although Alper (2011) found that families from middle to higher socioeconomic statuses might not fully support new media use "due to 'moral panics' regarding popular culture and digital technologies" (p. 180), our findings suggest that parental concerns are socially constructed and are not specific to socio-economic status.…”
Section: Discussioncontrasting
confidence: 75%
“…Taken together, expert opinion and contemporary research now recommend that parents, caregivers, and educators approach media as another learning resource (Alper, 2011), basing their decisions about use on evidence regarding the promise and potential benefits of media as well as possible harm rather than ungrounded advocacy. In particular, experts call for a reexamination of "screen time" as a primary measure of children's exposure to Downloaded by [Northwestern University] at 15:45 05 June 2016 media, arguing instead for a more sensitive metric that captures "developmentally appropriate technology use" to guide decisions about media use for young children (e.g., Daugherty, Dossani, Johnson, & Wright, 2014).…”
Section: State Of Educational Mediamentioning
confidence: 96%
“…Bajo esta óptica, el comportamiento informacional es una variable evaluable muy significativa en redes sociales, por tanto en metaliteracy. Este criterio se fundamenta, además, en la noción de cognición distribuida, esto es, la capacidad la interactuar significativamente con las personas que apoyan nuestro aprendizaje mediante sus propios conocimientos o procedimientos y prácticas (Alper, 2013).…”
Section: Metodología Didáctica Y Evaluación De Competencias En La Metunclassified